Pelaksanaan Jual Beli Tanah Melalui Jasa Perantara (PT. Lobi utama) di Kota Batam - Lendrawati Lendrawati; Rina Kusniati (Fakultas Hukum, Universitas Internasional Batam, 2017)
It is important to provide a guarantee and assurance to prospective buyers in order to avoid unwanted legal problems and could harm the buyer later after the parties managed to make the process of buying and selling land. If it is in accordance with the wishes and reached an agreement on the price of buying and selling land, it will proceed to the signing of the sale and purchase of land in front of the Notary/PPAT. After the stage of signing the deed of sale and purchase of land is reached and the buyer has paid the price of the sale and purchase of land previously agreed, the intermediary will receive a commission agreed upon with the seller/owner of the land previously as a form of appreciation. This research method is normative law by using secondary data obtained from observation and review of the literature. Processing and analysis of legal materials in the research conducted descriptively. Research result in the conclusion is the implementations of the land purchase through an intermediary (PT. Lobi Utama) in the operations against the sale and purchase of land deemed to have fulfilled all the conditions or rules in force in Indonesia. Intermediate types run by PT. Lobi Utama is kind of an intermediate form of the commissioners, especially the commissioner acting on behalf of the principal (acting on behalf of the seller).